Interaction Networks Converging on Immunosuppressive Roles of Granzyme B: Special Niches Within the Tumor Microenvironment - Wang, Weinan; Zou, Rui; Qiu, Ye; Liu, Jishuang; Xin, Yu; He, Tianzhu; Qiu, Zhidong (Frontiers in Immunology, 2021)
Granzyme B is a renowned effector molecule primarily utilized by CTLs and NK cells against ill-defined and/or transformed cells during immunosurveillance. The overall expression of granzyme B within tumor microenvironment has been well-established as a prognostic marker indicative of priming immunity for a long time. Until recent years, increasing immunosuppressive effects of granzyme B are unveiled in the setting of different immunological context. The accumulative evidence confounded the roles of granzyme B in immune responses, thereby arousing great interests in characterizing detailed feature of granzyme B-positive niche. In this paper, the granzyme B-related regulatory effects of major suppressor cells as well as the tumor microenvironment that defines such functionalities were longitudinally summarized and discussed. Multiplex networks were built upon the interactions among different transcriptional factors, cytokines, and chemokines that regarded to the initiation and regulation of granzyme B-mediated immunosuppression. The conclusions and prospect may facilitate better interpretations of the clinical significance of granzyme B, guiding the rational development of therapeutic regimen and diagnostic probes for anti-tumor purposes.